Al-jamiat al-islamiyah wa dawruha al-raid fi al-Tarbiyah wa Tanmiyah al-Thaqafah - Sidqon Maesur (Indonesian Journal of Islam and Muslim Societies, 2011)
Islamic University has become a pioneer in the field of education and cultural development for years. The material taught includes Humanities, sociology and various applied science. Some earlier Islamic universities in the past are the University of al-Azhar, Fusthat, Qurawiyin, Mustanshiriyah, Nidhamiyah, and Qordoba. The former Islamic scholars actively created new theories which have not been existed before. Similarly Islamic Univiersities in any level have important role in the development of culture through a variety of programs, by preparing cadres who have scientific competence so that they are ready in the dissemination of Islamic culture that aims to build an ideal and realistic Islamic society and realistic